Policy options for advancing seed systems for vegetatively propagated crops in Vietnam - Gatto, M.; Le, Dung Phuong; Pacillo, Grazia; Maredia, Mywish K.; Hareau, Guy; Spielman, David J.; Labarta, Ricardo Antonio (Informa UK Limited, 2021)
Seed systems for vegetatively propagated crops (VPCs) are frequently governed by regulatory blueprints designed for major cereal crops. This approach tends to disregard the distinct biological characteristics of VPCs, thus limiting farmers’ access to high-quality planting material and increasing the risk of pest and disease transmission. In this paper, we ask what type of regulatory framework is appropriate for improving farmers’ access to quality VPC planting material and what the costs, benefits, risks, and unintended consequences are of alternative regulations. We explore this in the context of cassava (Manihot esculenta) and potato (Solanum tuberosum) in Vietnam through secondary data, key informant interviews, and focus-group discussions. Findings indicate that despite a regulatory regime that imposes strict rules on the production and trade of planting material for VPCs, the market is largely unregulated because of weak enforcement capacity. Instead, producers and traders of VPC planting material signal quality to farmers through trust, reputation, and long-term relationships. Though effective at a localized scale, these informal systems are unlikely to accommodate expansion of the cassava and potato sectors and unlikely to prove effective in managing increases in pest and disease pressures that result from cross-border trade or climate change. We discuss alternative policy approaches and argue that the most appropriate policy regime requires a careful balance between a permissive regime at the local level and strict regulatory surveillance and enforcement at the national and regional levels. These approaches provide lessons for other developing countries where VPCs are important for economic growth and agricultural development.